Differentiation between Triatoma arthurneivai and Triatoma wygodzinskyi (Hemiptera: Reduviidae: Triatominae) using cytotaxonomy - Alevi, K. C. C. [UNESP]; Imperador, C. H. L. [UNESP]; Moreira, F. F. F.; Jurberg, J.; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2016)
Using classic morphometric techniques to examine the head and thorax of Triatoma specimens, researchers identified a possible taxonomic problem involving T. arthurneivai (Lent & Martins) and T. wygodzinskyi (Lent). A recent geometric morphometric study indicated that the insects captured outside the Serra do Cipo region, State of Minas Gerais, Brazil, were T. wygodzinskyi. The misidentification of T. arthurneivai as T. wygodzinskyi could result in several problems associated with entoepidemiological lifting, the biological characterization of the species, and phylogenetic reconstruction. For the first time, we describe the use of cytogenetic analysis as a tool for differentiation between T. arthurneivai and T. wygodzinskyi. The results indicated that both species had the same number of chromosomes 2n = 22 (20A + XY). However, analyses of spermatocytes during early prophase indicated that it was possible to differentiate T. arthurneivai and T. wygodzinskyi, because only T. arthurneivai exhibited heteropycnotic blocks distributed in the chromatin. Therefore, we highlight the analysis of spermatocytes as a taxonomic tool for the characterization of T. arthurneivai and T. wygodzinskyi, and suggest that the technique can be used for entoepidemiological lifting in vector control programs. Thus, the results presented here, in conjunction with morphometric analyses, are of utmost taxonomic and epidemiological importance for the identification of T. arthurneivai and T. wygodzinskyi specimens.
Keywords: Cytogenetics; Taxonomy; Maculata subcomplex